Mitigating oxygen release in anionic-redox-active cathode materials by cationic substitution through rational design. Issue 47 (26th November 2018) - Wynn, Thomas A.; Fang, Chengcheng; Zhang, Minghao; Liu, Haodong; Davies, Daniel M.; Wang, Xuefeng; Lau, Derek; Lee, Jungwoo Z.; Huang, Bo-Yuan; Fung, Kuan-Zong; Ni, Chung-Ta; Meng, Ying Shirley
Abstract : Density functional theory is coupled with experiment to explore the ability of substitutional doping to improve oxygen stability in Li-rich layered oxide bulk. Abstract : When substituting excess lithium in the transition metal layer, oxygen extends its role as a framework in classical layered oxide cathodes, exhibiting electrochemical activity and enhancing the reversible capacities of layered oxides through anionic redox mechanisms. However, oxygen activity comes with instability in the form of oxygen loss, which is associated with irreversible voltage decay and capacity fade. To understand this irreversible loss and to increase the stability of lattice oxygen, density functional theory is applied to calculate oxygen vacancy formation energies in lithium rich transition metal layered oxides for a variety of dopants, noting increased stability upon doping with 4d elements Mo and Ru. Driven by these findings, Mo is co-doped with Co into Li[Li0.2 Ni0.2 Mn0.6 ]O2, showing notably reduced voltage decay and capacity fade without sacrificing energy density and cycle life, and the evidence of Mo incorporation is presented. Calculations suggest that this is due to a modified charge density distribution around anions upon incorporation of Mo, altering the local band structure and impeding oxygen vacancy formation, while maintaining the anionic activity available for redox.